Dynamics and Control of Noncooperative Space Target Capture Using a Flexible Manipulator - Kang-Hao Wang; Ru-Hao Wang; Xiao-Feng Liu; Yu-Lei Fu; Guo-Ping Cai (International Journal of Aerospace Engineering)
The capture of noncooperative space targets is an important research topic in the aerospace field. Although a lot of research has been done, capturing remains a significant challenge, particularly when using a flexible manipulator. In this paper, the dynamic modeling and control problems of capturing a noncooperative spacecraft using a long-span flexible manipulator are investigated. Firstly, a modified model is presented to describe the flexibility of the manipulator arising from both its links and joints, in which the flexibility of the joint is considered as an elastic constraint of links. Additionally, we provide the frequency and mode functions of this model and derive the dynamic equations of the flexible manipulator based on the floating frame of reference formulation. Secondly, this paper employs the position–based damping control method to design the capturing controller. A simulation example of capturing a tumbling spacecraft in three dimensions is presented. The simulation results show that the designed control method can quickly eliminate vibration and achieve stable contact retention for at least 3 s when capturing noncooperative spacecraft.